Verbs of Motion in English, Croatian and French: How prototypical syntactic environments determine paradigmatic lexical organization - Žic Fuchs, Milena (1997)
Verbs of motion have been a very much discussed topic both from the semantic and syntactic point of view. The main aim of this paper is to show how certain subgroups of semantically related verbs of motion in English, Croatian and French, show not only semantic relatedness but also reflect specific syntactic features. Thus by combining semantic feature analysis with the analysis of typical nuclear grammatical relations found in sentences containing verbs of motion, we can show that paradigmatic structures can be more readily determined by integrating semantics and syntax. The general principle that emerges from the analysis of verbs of motion in the three languages, shows that the basic prototypical meanings are realized in prototypical syntactic environments, while changes on the syntagmatic level (on the basis of the more or less principle) show polysemous effects which in peripheral cases bring about changes in meaning that "transform" verbs of motion into verbs belonging to other semantic fields. An analysis of this kind sheds additional light on how verbs interact with lexemes on the sytagmatic level and with semantically related lexemes on the paradigmatic level, showing thus through their mutual interaction, that the notion of prototype can be seen as a link that connects syntagmatic relations and paradigmatic "semantic fields".
Projekt MZOS
ENG